Minorités et frontières politiques. Essai en hommage au professeur Éric Schwimmer - Bariteau, Claude (Anthropologica, 2022)
This paper argues that the analytical framework of "Symbolic Competition" (Schwimmer 1972) reappears in Schwimmer's Le Syndrome des Plaines d'Abraham (1995). This framework becomes peripheral in "Linstallation de la lutte" ("Setting up the struggle") where Schwimmer proposes that the struggle of the Quebecois people, like that of all people in similar situations, is based in civil society rather than the provincial political arena. This paper also serves as testimony to the influence of Eric Schwimmer on my reflections which, through different activities, led me to a better understanding of his thought and to discovering that setting up the struggle must have as a goal the establishment of political authority and the foundations of "living together."